A brief overview of the marine environmentally friendly anti-fouling surface strategy - Yusuf, Yusliza; Mohammad Taha, Mastura; Omar, Nooririnah; Ghazali, Mariyam Jameelah (SAGE Publications Ltd, 2023)
Fouling that develops on the surface of maritime environmental components, such as hulls and pipelines, can lead to various adverse effects and large losses to the company. Living organisms such as bacteria, algae, and shellfish, as well as organic and inorganic materials, settle on the surface and can affect function and productivity. The development of anti-fouling surfaces, such as surfaces containing chemicals that are biocidal agents, has long been used. However, the usage has been banned because of marine environmental effects. In this review, the current state of strategy for the fabrication of an environmentally anti-fouling surface that is suitable for marine environments is discussed. Several strategies for producing environmentally friendly anti-fouling surfaces have been established, such as the development of surfaces with antibacterial and self-cleaning properties, and have been successfully implemented in other fields such as textiles, medicine, and buildings. Among the methods that may be used are the development of surfaces that include biocides; surfaces that inhibit and prevent bacterial adhesion; and surfaces that have components that can kill bacteria when contacted. Self-cleaning surfaces, on the other hand, can be made by creating surfaces with superhydrophobic or superhydrifilic wettability properties, as well as photocatalytic surfaces with self-cleaning properties that can be used in the marine environment.